2016
DOI: 10.1039/c6cp01493c
|View full text |Cite
|
Sign up to set email alerts
|

High resolution GHz and THz (FTIR) spectroscopy and theory of parity violation and tunneling for 1,2-dithiine (C4H4S2) as a candidate for measuring the parity violating energy difference between enantiomers of chiral molecules

Abstract: We report high resolution spectroscopic results of 1,2-dithiine-(1,2-dithia-3,5-cyclohexadiene, C4H4S2) in the gigahertz and terahertz spectroscopic ranges and exploratory theoretical calculations of parity violation and tunneling processes in view of a possible experimental determination of the parity violating energy difference ΔpvE in this chiral molecule. Theory predicts that the parity violating energy difference between the enantiomers in their ground state (ΔpvE ≃ 1.1 × 10(-11)(hc) cm(-1)) is in princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 122 publications
0
15
0
2
Order By: Relevance
“…70) Beispiele sind das HOOH-analoge ClOOCl-Molekül 70,73,74) und das 1,2-Dithiin-Molekül. 75,76) Ein weiteres Beispiel ist Trisulfan. 77 72,96) Abb.…”
Section: Atomare Und Molekulare Tunnelprozesseunclassified
See 1 more Smart Citation
“…70) Beispiele sind das HOOH-analoge ClOOCl-Molekül 70,73,74) und das 1,2-Dithiin-Molekül. 75,76) Ein weiteres Beispiel ist Trisulfan. 77 72,96) Abb.…”
Section: Atomare Und Molekulare Tunnelprozesseunclassified
“…Messung der paritätsverletzenden Energieaufspaltung ∆ PV E. 72,96) 72,96) BTrendbericht Physikalische ChemieV trien der Potenziale, bei (hc)·10 −11 bis 10 −12 cm −1 (entsprechend 1 bis 0,1 feV) liegen. 70,[73][74][75][76][77] In diesen Fällen dominiert die Paritätsverletzung die Quantendynamik. 78) Die extrem kleinen Werte von Δ PV E lassen sich nach dem Schema in Abbildung 4a messen.…”
Section: Schritte Im Experiments Zurunclassified
“…In recent years, terahertz experimental methods have been widely applied in detecting biological and chemical molecules such as amino acids [1][2][3], saccharides [4,5], DNA nucleobases [6], and even harmful and dangerous materials such as pesticides [7,8], narcotics [9], and explosives [10]. e reasonable explanation for these popular applications is that THz-TDS is highly sensitive to similar materials with relatively subtle differences [11]. Meanwhile, an increasing number of researches have been done, and it was found that most organic molecules in solid state have rich and distinct spectra in the frequency region among 0.1-6.0 THz [12].…”
Section: Introductionmentioning
confidence: 99%
“…The barrier for inversion by ring puckering is ∼2500 cm –1 (in wavenumbers), of appropriate magnitude. While the infrared spectra in the higher wavenumber ranges can be partly analyzed on the basis of FTIR spectra using ordinary light sources, the important lowest frequency fundamentals fall in the terahertz range ν = 5 to 8 THz (ν̃ = 165 to 284 cm –1 as summarized in Figure ), very difficult for traditional FTIR spectroscopy but accessible to highest resolution FTIR spectroscopy using synchrotron light sources as available at the Swiss Light Source (SLS). , We report here a first successful analysis of the spectra of 1,2-dithiine in this range.…”
mentioning
confidence: 99%
“…The FTIR spectra of 1,2-dithiine (C 4 H 4 S 2 ) as synthesized following ref (and refs cited therein) were recorded with the ETHSLS-2009 Bruker prototype using synchrotron radiation in the range 200 to 340 cm –1 . This prototype spectrometer has a resolution corresponding to an unapodized instrumental bandwidth of 0.00053 cm –1 (16 MHz), which is currently the highest for a FTIR spectrometer worldwide.…”
mentioning
confidence: 99%